Analisis Faktor-Faktor Penyebab Pembiayaan Bermasalah pada Akad Murabahah dan Proses Penyelesaiannya di BMT Harapan Ummat Tulungagung - Mohammad Saiful Rifai; Nurwahyuni Nurwahyuni; Chosinawarotin Chosinawarotin (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2024)
Indonesia's population, which exceeds 280 million, is not accompanied by a sufficient number of job opportunities. The difficulty in finding employment has led to high unemployment rates. This situation forces the society to become more creative in generating income, one of which is by starting a business. Running a business requires a considerable amount of capital, especially with the rising prices of goods. Murabahah financing is one solution to address this issue. Murabahah is a sale and purchase agreement between a customer and a financial institution, with an agreed-upon margin value. BMT Harapan Ummat Tulungagung is one of the financial institutions offering this service. This study aims to examine the standard assessment of the feasibility of Murabahah financing approval, the factors causing problematic financing, and the resolution stages. The research adopts a phenomenological approach with a field research type using a descriptive qualitative method. The findings reveal that the feasibility assessment of potential customers for financing approval is based on the 5C principle. First, Character is assessed through interviews with the customer and cross-checked with the local community. Second, Collateral refers to the requirement that financing must be secured by collateral such as land or building certificates, civil servant identification (SK ASN), or vehicle registration certificates (BPKB) for motorbikes or cars. Third, Capacity is evaluated from the financial reports of the business, salary slips, employment status, and business location surveys for self-employed customers. Fourth, Condition is assessed from internal factors such as the economic status and the number of dependents, and external factors such as the environmental conditions. Fifth, Capital is evaluated from the physical evidence of the ongoing business and can also be measured by the assets owned. The factors causing problematic Murabahah financing in BMT Harapan Ummat Tulungagung from external factors include: 1) educational expenses; 2) daily living expenses; 3) business disruptions; 4) unpaid receivables; and 5) existing loans from other places. Internal factors include the absence of penalties for problematic financing in the agreement letter, which ultimately leads customers to neglect their obligations. The resolution stages for problematic financing in BMT Harapan Ummat Tulungagung are: 1) contacting the customer through messages and phone calls; 2) visiting the customer's residence, either with or without prior agreement; 3) negotiating installment payments through restructuring or selling the Murabahah collateral to cover the remaining payment obligations; and 4) waiting for the customer to acknowledge the need for payment. The final stage occurs when the customer cannot be contacted or met.